The challenge of making a long-term commitment when dealing with an urgent situation - F. Villalba, Lucía (Ánima, 2025)
This work navigates the question of political immobilism in the present moment, and seeks to understand the relationship between climate change, inaction in the face of it, and the absence of alternatives for political systems. To do so, it draws upon Hans Ulrich Gumbrecht’s diagnosis of the broad present. Likewise, this work traverses Fisherian propositions regarding capitalist realism and the cancellation of the future. At the same time, to link the processes of capitalist exploitation, production, and accumulation with changes in nature, this analysis employs Jason W. Moore’s thinking. Through this approach, this work attempts to highlight the need to commit and construct an emancipatory politics in the face of the climate emergency.